Repair bond strength of microhybrid, nanohybrid and nanofilled resin composites: Effect of substrate resin type, surface conditioning and ageing - Özcan, Mutlu; Corazza, Pedro Henrique [UNESP]; Marocho, Susana Maria Salazar [UNESP]; Barbosa, Silvia Helena [UNESP]; Bottino, Marco Antonio [UNESP] (Springer Nature, 2013)
Objectives: This study evaluated the microtensile bond strength (MTBS) of non-aged and aged resin-based composites (RBC) (nanohybrid and nanofilled) after two surface conditioning methods, repaired using the composite of the same kind or a microhybrid composite. Materials and methods: Nanohybrid (Tetric EvoCeram-TE) and nanofilled (Filtek Supreme-FS) RBC blocks (5 × 5 × 6 mm) (N = 128) were fabricated and randomly divided into two groups: (a) no ageing (control group) and (b) ageing (5.000 thermocycling, 5-55 °C). RBC surfaces were polished by up to 1,200-grit silicone carbide papers and conditioned with either (a) air abrasion with 30-μm SiO2 particles (CoJet Sand) for 4 s + silane coupling agent (ESPE-Sil) + adhesive resin (VisioBond) (n = 16) or (b) adhesive application only (Multilink A+B for TE; Adper ScotchBond 1XT for FS) (n = 16). In half of the groups, repair resin of the same kind with the RBC and, in the other half, a different kind of composite (microhybrid, Quadrant Anterior Shine-AS) with its corresponding adhesive (Quadrant UniBond) was used. The specimens were submitted to MTBS test (0.5 mm/min). Data were analysed using three-way ANOVA and Tukey's tests. Degree of conversion (DC) of non-aged and aged resin composites (TE, FS) (n = 3 per group) was measured by micro-Raman analyses. Results: RBC type (p = 0.001) and ageing affected the MTBS results significantly (p = 0.001). Surface conditioning type did not show significant difference (p = 0.726), but less number of pre-test failures was experienced with the CoJet system compared to adhesive resin application only. Repair strength on aged TE showed significantly less (p < 0.05) MTBS than for FS. FS repaired with the same kind of RBC and adhesive resin presented the highest cohesive failures (43 %). DC was higher for TE (71 %) than for FS (58 %) before ageing. Conclusion: On the aged RBCs, less favourable repair strength could be expected especially for nanohybrid composite. For repair actions, RBC surface conditioning could be accomplished with either adhesive resin application only or with CoJet system, providing that the latter resulted in less pre-test failures. Clinical relevance: Clinicians could condition the resin surface prior to repair or relayering with either CoJet system or adhesive resin application only, depending on the availability of the system. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Ageing; Microtensile bond strength; Minimal invasive dentistry; Repair; Resin composite; Surface treatment